Does Internet Censorship Reduce Crime Rate? - Karnadi, Erwin Bramana (CommIT (Communication and Information Technology) Journal, 2015)
The study examines the relationship between Internet censorship and crime rate. Classical  views  of censorship  suggest that filtering contents  that are per- ceived as negative such as violence and pornography  can have a negative impact on crime rate. However,  there is no evidence to suggest  any causal relationship  between censorship  and crime rate. The Internet has  made it easier for individuals  to access  any information  they want, and hence Internet Censorship  is applied  to filter contents that are deemed negative. We discussed several approaches that may be used to estimate the relationship between  Internet Censorship  and Crime Rate, and we decided  to use  OLS. We  found that Conflict Internet Censorship  is the only type of Internet censorship that has a significant negative impact on Crime Rate. Furthermore, it only significantly affects Crime Rate for highly educated countries.